X-ray spectrum estimation from the transmission method using the radioluminescence of an Al2O3:C crystal - Rui Chen; Qingxian Zhang; Jian Zhang; Liangquan Ge; Yi Gu; Rui Yang; Hui Li; Qiushi Liu; Zhiqiang Cheng; Yi Lin (Nuclear Engineering and Technology)
The X-ray spectrum of X-ray tube is crucial for radiation dose calculations. Due to the high photon flux, it is difficult to directly measure the primary spectrum of X-ray tube. Transmission measurement is one of indirect method used to determine the primary spectrum of X-ray tube. Although the method is experimentally simple, X-ray spectrum estimation from transmission method is a seriously ill-conditioned problem. In this paper, a new transmission measurement instrument with an the Al2O3:C crystal detector is proposed. Real-time dose rate attenuation data from transmission method are collected by using the radioluminescence(RL) of the Al2O3:C crystal. The expectation-maximization (EM) method is applied for X-ray spectrum estimation from transmission method. The method is demonstrated on typical simulated spectra of 80,100,120,140 and 160 kV from X-ray tubes. The X-ray spectra are simulated with the Monte Carlo code Geant4. The EM method is successfully applied to seriously ill-conditioned and under determined estimation problems. The results showed that the X-ray spectrum estimation method is a robust technique for estimating the primary spectrum of X-ray tube, and that the new instrument for transmission measurements can be used to accurately estimate X-ray spectrum.